TINJAUAN YURIDIS PEMBERIAN REMISI BAGI NARAPIDANA TINDAK PIDANA NARKOTIKA DAN PSIKOTROPIKA DITINJAU DARI UNDANG-UNDANG NOMOR 12 TAHUN 1995 TENTANG PEMASYARAKATAN : Studi di LAPAS Klas IIA Serang - Sigit Kamseno (Gapenas Publisher, 2022)
Rights of prisoners stipulated in the Law No. 12 of 1995 concerning on correctional. In article 14, it is explicity mentioned some prisoners rights including the right to get remission. The implementation of the entitlement remissions for the prisoners of narcotics and psychotropic crimes and certain criminal offenses categorized as extra ordinary crime regulated in The Government Regulation No. 99 of 2012 on the second amandement of the Goverment Regulation No. 32 of 1999 on the requirement and procedures for the implementation of the prisoners rights. In this government regulation, remission for the prisoners of narcotics and psychotropic cases and specific criminal acts enforced differently from other general crimes. Policy about tightening these remissions raise the pro and contra in the society. In the one hand, those who agree on the policy argue that the perpretactors of narcotics and psychotropic cases are not feasible to be given remission, because narcotics and psychotropic are extra ordinary crimes. This can evoke deterrent effect. On the other hand, people whose counter with this policy assume that remission is a right of prisoners that have been regulated by laws. Restrictions remissions by tightening of the requirement for prisoners of certain criminal acts are form discrimination that violated human rights. This research aim are finding out on the the implementation of remission in Prison of Serang and how it is answered based on human right perspective. This research is a normative legsl research bu using a qualitative method. Collecting data with interview with The official of Prison Serang and some narcotics prisoners. The result of this research concludes that remission for the prisoners of certain criminal acts categorized as a extra ordinary crime including the narcotics and psychotropic cases enforced differently regulated specifically in the Government Regulation No.99 of 2012 in addition to meet the requirement of good behavior, inmates must also have been serving a criminal sentence of more than 6 (six) months, must also be willing to cooperate with law inforcement to help dismantle the criminal case that done by them, also should have paid the full of compensation in accordance with the court decision. Remission is a fundamental rights that must be granted. And the prison of Serang have been conduct the implementation for the prisoners of narcotics and psychotropic based on Law No.12 of 1995. There is no discriminatory treatment for the prisoners to get their rights for remissions. The implementation of remission rights in Prison of Serang is not violated against the human rights